INTERACTIVE RADIO ON MONEY, FINANCIAL TECHNOLOGY, AND PSYCHOLOGY OF MONEY: SMART FINANCIAL MANAGEMENT IN THE MIDST OF A CRISIS - Renna Magdalena; Yanuar Dananjaya (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The implementation of Community Service (Pengabdian Kepada Masyarakat/PKM) for December 2025 was carried out by a team from the Faculty of Economics and Business, Universitas Pelita Harapan Surabaya Campus, in collaboration with Radio Sangkakala Surabaya. The primary objective was to deliver broader financial education to the community by presenting qualified academic speakers from the Management and Accounting Study Programs. The activity was conducted in an interactive talkshow format under the overarching theme "Interactive Radio on Money, Financial Technology, and Psychology of Money: Smart Financial Management in the Midst of a Crisis." Two sessions were held: the first on December 2, 2025, covering "Money and Technology in the Midst of a Crisis" by Dr. Renna Magdalena, and the second on December 16, 2025, covering "Psychology of Money" by Dr. Yanuar Dananjaya. The results demonstrated that this PKM activity successfully enhanced public awareness of financial literacy, digital financial technology utilization, and the psychological dimensions of financial decision-making. This initiative confirms that academic-media collaboration through radio serves as an effective and inclusive channel for financial education, particularly in reaching productive and financially vulnerable community groups in the Surabaya area